Anticipated impacts of voluntary assisted dying legislation on nursing practice. (September 2022) - Snir, Jessica T; Ko, Danielle N; Pratt, Bridget; McDougall, Rosalind
Background: The Voluntary Assisted Dying Act 2017 passed into law in Victoria, Australia, on the 29 November 2017. Internationally, nurses have been shown to be intimately involved in patient care throughout the voluntary assisted dying process. However, there is a paucity of research exploring Australian nurses' perspectives on voluntary assisted dying and, in particular, how Victorian nurses anticipate the implementation of this ethically controversial legislation will impact their professional lives. Objectives: To explore Victorian nurses' expectations of the ethical and practical impacts the voluntary assisted dying legislation will have on their professional lives. Research design: This qualitative study analysed nurses' free text responses collected as part of a larger mixed methods online survey investigating staff views on the Voluntary Assisted Dying Act. Data were collected during the period between the passing of the voluntary assisted dying legislation and the start date and were analysed using inductive content analysis. Participants and research context: Free text survey responses were analysed from 1873 nurses employed across seven Victorian health services located in both metropolitan and regional areas of the state. Ethical considerations: The study obtained research ethics approval and all participants were informed of the voluntary and anonymous nature of their participation. Findings: This study identified three broad areas of Victorian nurses' professional lives that they expected to be impacted by the implementation of voluntary assisted dying: professional identity, career development and workplace relationships. Conclusion: Participants anticipate diverse and nursing-specific impacts of the implementation of voluntary assisted dying in Victoria. Their insights can inform health services in jurisdictions considering or already implementing voluntary assisted dying, to develop policies, procedures and staff training programmes that safeguard the well-being and legal rights of their nursing staff.